Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Raptis, Dimitrios; Maak, Matthias; Krautz, Christian; Merkel, Susanne; Brunner, Maximilian; Agaimy, Abbas; Hartmann, Arndt; Semrau, Sabine; Ott, Oliver; Fietkau, Rainer; Siebler, Jürgen; Grützmann, Robert; et al. (Archives of Medical Science, 2024)
Introduction: Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival. Material and methods: Between 2001 and 2014, 590 patients with a diagnosis of gastric cancer underwent surgery in our institution, including 120 Siewert type II/III carcinomas of the esophagogastric junction. All patients underwent distal resection of the stomach, gastrectomy or total gastrectomy combined with transhiatal distal esophageal resection. All operations included D2-D3 lymph node dissection (LND). Data were recorded by the cancer registry of the department of surgery and analyzed retrospectively. Results: The patients were classified according to the TNM (UICC 2010) and Lauren classification. 29% of the patients underwent primary surgery and 31% received neoadjuvant therapy. The median number of harvested lymph nodes was 33 for patients diagnosed with gastric cancer, and 29 for esophagogastric adenocarcinomas, respectively. The anastomotic leak rate was 3%. In this study, the 5-year overall survival rate was 51% concerning gastric carcinomas, 44% for Siewert type II and 47% for Siewert III cancers of the esophagogastric junction. Conclusions: Increased survival with low complication rates were achieved after individualized and multimodal treatment concepts combined with consistently applied extended lymphadenectomy.
CRIS-Team Scopus Importer:2024-04-19
Keywords: D3 dissection; gastric cancer; Siewert II/III